Tourism Development Policy Through Economic Potential in Supporting Tourism and Creative Economy Programs in the Lake Toba Region - Siti Hajar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
If implemented with optimal planning, tourism development will encourage economic growth and improve people's welfare. However, if tourism development does not go through good planning, it will hurt people's lives around the Lake Toba area. Efforts to develop tourism objects in terms of economic potential by increasing the diversity and competitiveness of local community products and facilitating and fostering community tourism businesses through tourism marketing programs. Tourism development also opens up job opportunities and can build regional economies and local communities in tourism areas such as Lake Toba. Various economic potentials that can be developed in the Lake Toba area include improving the quality of local community handicrafts such as making sculptures, souvenirs, and weaving, which carry the characteristics of the Lake Toba region. The method used in this study is a qualitative research method and analyzed by SWOT analysis. The results of this study generate opportunities and challenges in developing tourism in the Lake Toba region through planning for the economic potential so that there is a grouping of economic potential according to its type. The advantages of the developed economic potential are characteristic of the area around the Lake Toba area and becoming a supporter of the development of Lake Toba tourism. One of the results is realizing a tourist village which is the hallmark of tourism in Samosir Regency, namely Ulos Village in Lumban Suhi Suhi Touran Village.